A study on the demand for a University of the Philippines Manila training program in Occupational and Environmental medicine (NIH 2008-029) - Macaraeg, Perla S.
A study utilizing self-administered questionnaires and focused group discussions (FGDs) was conducted to assess the need for specialty training in Occupational and Environmental Medicine (OEM) and to determine the views and opinions of potential trainees and of stakeholders regarding its importance. Five hundred and forty-two (542) respondents were covered by the survey and eight (8) groups composed of potential trainees and/or stakeholders participated in the FGDs conducted at Subic and Clark Economic Zones at Cavite, Laguna, Batangas and in various government and non-government offices and hospitals. Overall response rates were highly favorable on statements regarding the importance of a specialty training program in OEM. Expected competencies and the training components of the proposed OEM training program were rated as very important by majority of the respondents. In all study groups, majority (52.6% - 73.8%) expressed intention to undergo specialty training in OEM. Approximately one-third (33.2%) of the respondents preferred a 2-year post residency OEM training program, however, other modes of training such as the 3-4 year residency program, modular courses, training by distance education and even online courses were also suggested. It is therefore strongly recommended that University of the Philippines Manila should respond to calls from various sectors for the institution of a training program that enables the medical practitioner to face the challenges of industrialization, urbanization, and a growing number of working population and communities exposed to occupational and environmental hazards
Unpublished collaborative research/study by UP Manila professors and health professionals for a training program in occupational and environmental medicine
Keywords: Occupational Medicine